Osteoimmunology: A Current Update of the Interplay Between Bone and the Immune System - Guder, Christian; Gravius, Sascha; Burger, Christof; Wirtz, Dieter C.; Schildberg, Frank A. (Frontiers in Immunology, 2020)
Immunology, already a discipline in its own right, has become a major part of many different medical fields. However, its relationship to orthopedics and trauma surgery has unfortunately, and perhaps unjustly, been developing rather slowly. Discover-ies in recent years have emphasized the immense breadth of communication and connection between both systems and, importantly, the highly promising therapeu-tic opportunities. Recent discoveries of factors originally assigned to the immune system have now also been shown to have a significant impact on bone health and disease, which has greatly changed how we approach treatment of bone pathologies. In case of bone fracture, immune cells, especially macrophages, are present through-out the whole healing process, assure defense against pathogens and discharge a complex variety of effectors to regulate bone modelling. In rheumatoid arthritis and osteoporosis, the immune system contributes to the formation of the pathological and chronic conditions. Fascinatingly, prosthesis failure is not at all solely a me-chanical problem of improper strain but works in conjunction with an active contri-bution of the immune system as a reaction to irritant debris from material wear. Unravelling conjoined mechanisms of the immune and osseous systems heralds therapeutic possibilities for ailments of both. Contemplation of the bone as merely an unchanging support pillar is outdated and obsolete. Instead it is manda-tory that this highly diverse network be incorporated in our understanding of the immune system and hematopoiesis.